Aspects of financial liberalisation and capital market development in the Caribbean - Craigwell, Roland (Central Bank of Barbados BridgetownBB, 2007)
Analyzes the likely influences of liberalisation in the Caribbean region on financial stability, maintenance of the exchange rate, international reserves, the development of the financial sector, competition and economic growth.